(untitled) (Eurasian Journal of Ecology, 2021)
Pollution and drainage of surface waters is a global and national environmental problem. This article presents the results of the dynamics of hydrophysical, hydrochemical indicators and water quality in Lake Maloe Chabachye of the State National Natural Park “Burabay” by seasons for 2016-2020. The dynamics of the content of biogenic elements and heavy metals; degree and chemistry of salinity, as well as pollution index and water quality class have been studied. The research results have showed that in term of water smell, color, pH, content of dissolved oxygen, biochemical oxygen demand and general iron, the water in the lake corresponds to the maximum permitted concentration.The chemical oxygen demand, mineralization degree, the content of ammonium ions, fluorides, chlorides, sulfates, manganese, copper and zinc exceeds the maximum permitted concentration. Seasonal dynamics analysis showed darkening of water color in spring. Dissolved oxygen content in winter and spring exceeded the norm by 2.8 and 2.4 times; in summer and autumn – 2 and 2.1 times. Chemical oxygen demand in winter and summer periods exceeded the norm by 6.6 and 6.7 times; in spring and autumn – by 4.9 and 4.4 times. There was a decrease in fluoride content in spring and autumn. In winter and summer the water was salty; in spring and autumn it was brackish. Dangerous water pollution with copper cations was evaluated in spring and autumn. An excess of zinc content was noted in September. According to the pollution index (1.1-1.2), the water in the lake corresponds to the 3rd class of pollution. According to the Unified Quality Classification, the water in the lake belongs to the 4 th class (in terms of biochemical and chemical oxygen demand, the content of copper, manganese, zinc and iron –the 1 stclass; ammonium –the 2nd class; sulfates –the 4th class; magnesium, mineralization, fluorides and chlorides –the 5th class of pollution). Key words: lake, hydrophysics, hydrochemics, mineralization, pollution.